Diuretic resistance and heart failure: between the congestion and kidney injury - Morejón-Barragán, Paola (2020)
Nowadays, heart Failure (HF) is one of the main contributors of cardiovascular morbidity and mortality, this faces us with great challenges. The heart-kidney interaction receives particular attention due to the development of the so-called cardiorenal syndrome (CRS) and the diuretic resistance, latter is a predictor of adverse events in acute HF and is independent of the glomerular filtration rate. Development of diuretic resistance is secondary to multiple causes, so a comprehensive evaluation of all of them is required. In recent years, congestion has become relevant within the pathophysiological mechanism of CRS, as it mutually generates and perpetuates damage in these two organs. Given the importance of congestion, diuretics remain the cornerstone of treatment, although their use is largely empirical due to the limited evidence available. The evidence-based treatment paradigm is elusive in this scenario, so one question remains unanswered: Do the interventions to treat or to prevent the diuretic resistance modify the prognosis in acute HF?